Nationalism in Badr Shaker Al-Sayyab’s Revolutionary Poetry and its Influence on Arabic Poetry - Shaimaa Hassanin (European Scientific Journal, ESJ, 2020)
This paper contends that Badr Shaker Al-Sayyab’s use of mythical and symbolic figures shows the impact of foreign and Arabic poetry on the history of humanity. It Appears that Al-Sayyab restored the ancient mythologies of his nation and exchanged this them with Anglo-American culture to handle the praxis of life and reflect the verifiable circumstances of the Middle East, particularly that of his nation, Iraq. This paper reevaluates Al-Sayyab’s poetry from a different perspective which reflects the socio-political unsetting within the Middle East. Al-Sayyab does not essentially duplicate Eliot’s methods, symbolism and themes. Rather, he mixes them with his legendary vision to form a wealthy and widespread national poetry without neglecting or sacrificing the national orientations of his poems. The relationship between Al-Sayyab and other poets is one of subversion and alterations; not essentially one of a simple ongoing impact. Al-Sayyab progressed the myths utilized by Eliot and other poets and changed them to modernize his poetry. Critically, he utilizes myth in an organized and systematic way to compare the current subjects of his lyrics against inaccessible and legendary ones.